Design and Development of a Club Hunt Application Using PHP and Android - Sonali Mohanty; Jenil Bhakka; Jinal Dadhaniya; Mr. Amit Kumar; Dr. Nitin Mishra; Ms. Meenakshi Prajapati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Club Hunt is a site that is specifically made for students to make the process of finding and participating in campus clubs easier. This centralized system provides an easy-to-use interface for browsing different student organizations, such as academic, professional, recreational, and social clubs. Club Hunt allows students to search for clubs of interest, browse upcoming events, and network with peers. The platform increases student engagement and lessens the problem of fragmented discovery processes. Our solution features tailored recommendations, an extensive database, and mobile optimization to guarantee access. By connecting students with organizations, Club Hunt creates a richer and more diverse university community.